2020
DOI: 10.1136/bmjpo-2020-000671
|View full text |Cite
|
Sign up to set email alerts
|

Screening for caregiver psychosocial risk in children with medical complexity: a cross-sectional study

Abstract: ObjectiveTo quantify psychosocial risk in family caregivers of children with medical complexity using the Psychosocial Assessment Tool (PAT) and to investigate potential contributing sociodemographic factors.DesignCross-sectional study.SettingFamily caregivers completed questionnaires during long-term ventilation and complex care clinic visits at The Hospital for Sick Children, Toronto, Ontario, Canada.PatientsA total of 136 family caregivers of children with medical complexity completed the PAT questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 56 publications
4
22
2
Order By: Relevance
“…A tracheostomy tube for a child is not only associated with medical morbidity but also has important psychosocial effects on children and their families, including negative impacts on quality of life, sleep, relationships, social life, and employment. 4,5 As a result, decannulation of the tracheostomy tube is often a shared goal for patients, family caregivers, and their multidisciplinary care teams.…”
Section: Introductionmentioning
confidence: 99%
“…A tracheostomy tube for a child is not only associated with medical morbidity but also has important psychosocial effects on children and their families, including negative impacts on quality of life, sleep, relationships, social life, and employment. 4,5 As a result, decannulation of the tracheostomy tube is often a shared goal for patients, family caregivers, and their multidisciplinary care teams.…”
Section: Introductionmentioning
confidence: 99%
“…A one-sample t-test comparing PAT2.0 scores in our sample ( M = 1.177, SD = 0.771) with previous studies revealed that our sample had significantly higher levels of psychosocial risk compared to specific clinical pediatric samples, such as pediatric cystic fibrosis ( M = 1.00, SD = 0.77, N = 374) (Filigno et al, 2019 ) or pediatric cancer ( M = 1.021, SD = 0.700, N = 396) (Kazak et al, 2020 ). However, the total risk score in our sample was relatively similar to that of children with medical complexities (CMC) ( M = 1.170, SD = 0.740, N = 136) (Verma et al, 2020 ).…”
Section: Resultsmentioning
confidence: 54%
“…PAT scores of our cohort were seemingly lower than another study of parents of children with serious chronic illnesses, which showed their scores were among the highest of all previously studied pediatric populations, with 55% showing "Targeted" or "Clinical" risk. 33 Parental anxiety, but not depression, was also significantly higher when their child was intubated. Notably, parent emotional stress may be a sign that provider moral distress is also present (and vice versa), given that they correlate and all parties may recognize that the limitations of modern medicine to cure and of acute-illness-focused PICU care to address chronic needs.…”
Section: Discussionmentioning
confidence: 95%